Pigmentation PAX-ways: The role of Pax3 in melanogenesis, melanocyte stem cell maintenance, and disease - Kubic, Jennifer D. (2008)
Transcription factors initiate a program of gene expression and are catalysts in downstream molecular cascades that modulate a variety of cellular processes. Pax3 is a transcription factor that is important in the melanocyte and influences melanocytic proliferation, resistance to apoptosis, migration, lineage specificity and differentiation. In this review, we focus on Pax3 and the molecular pathways that Pax3 is a part of during melanogenesis and in the melanocyte stem cell. These roles of Pax3 are emphasized during the development of diseases and syndromes resulting from either too much or too little Pax3 function. Due to its key task in melanocyte stem cells and tumors, the Pax3 pathway may provide an ideal target for either stem cell or cancer therapies.